Calauan Municipal Hall the development of new town halls with respect to localization and inclusivity - Berris, Justin B.; Balane, Ronald S. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Calauan, Laguna is a tight-knit agricultural community but the sudden influx in the population has created a change in the social dynamics. It created a segregation between the old and new residents in the area. This influx also brought upon the need to create new facilities including a new town hall to better service the people. In fulfilling the need for a new town hall, this raises the issue on how the architecture of the town halls can help build trust, provide efficient service, and address the growing development of towns that befits the ever-changing dynamic between the citizens and the government. With Calauan municipal hall as a case example, the project aims to design a space that can help reunite a community through localization and inclusivity.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman